Persepsi Akuntan Publik dan Mahasiswa Akuntansi terhadap Kode Etik Profesi Akuntan pada Kantor Akuntan Publik dan Mahasiswa Akuntansi - Dewi Zulvia (JURNAL PUNDI, 2017)
This study aims to determine perceptions of Public Accountants and Accounting Students to the code of ethics of accounting profession. The analysis is based on respondents' answers obtained through questionnaires distributed in the city of Padang. The population of this research is Public Accountant residing in the town of Padang and Student of Accounting Department in Padang. This research uses sampling method. The selected sample is a Public Accountant who works at KAP in Padang City. In addition, the sample is also taken from Accounting Students who have taken the course of Auditing. To test the data normality, Statistical Pack For Social Science (SPSS) Kolmogorov-Smirnov Test method was used to test the difference of homogeneity of data variance using Statistical Packages for Social Science (SPSS) Test of Homogeneity of Variances. Hypothesis testing is done by using statistic analysis tool that is Independent Sample t-test by using SPSS help program. The results of this study indicate that there is a difference of perception between Public Accountant and Student Accounting Department to the code of ethics of the accounting profession.